Typification of clay-siliceous deposits of the Berezovskaya formation (on the example of wells of the Kharampurskoye field) - Klimova, E. S.; Chertina, K. N.; Alexandrov, M. A.; Solovieva, A. V.; Arzhilovskaya, N. N. (Litosfera (Ekaterinburg. Online), 2023)
Research subject. Clay-siliceous deposits of the Berezovskaya formation of the Cognac-Santon-Campanian age in three wells of the Kharampur deposit. Aim. To study the mineral and structural characteristics of the flint matrix for the separation of flint rocks into lithotypes, namely, silicites and flakes per se. Methods. X-ray diffraction analysis and scanning electron microscopy. Results and conclusions. The main criteria for the separation of flint rocks include the content of the opal-cristoballite-tridimite phase and its structural state, which is quantitatively characterized by the coefficient of structural perfection K (according to the X-ray diffraction) and, at the qualitative level, is confirmed by the difference in its morpholo gical types (according to the scanning electron microscopy). The relationship between the porosity of flint rocks and the sili con matrix microstructure was also established.